Analysis of The Need for Chemical Learning Media Based on Local Wisdom in Sitaro Islands - Leony Sanga Lamsari Purba; Santhya Anaomi Tamansa; Riska Yuna Peronika; Amsal Sukhendy Simaoju; Ikerman Jaya Harefa (Universitas Negeri Medan, 2024)
In the era of technology that continues to develop rapidly, students' needs for technology-based chemistry learning media are increasingly urgent. However, it cannot be denied that local wisdom also plays an important role in education. This research aims to analyze the needs of SMA MIPA students in Sitaro Regency for chemistry learning media based on technology and local wisdom. The research method used is quantitative descriptive. The results of data analysis show that the average score for all statement items is 3.99 on a Likert scale (maximum score 5), meaning that students generally agree with the use of learning media based on local wisdom. Further analysis shows that there is a significant difference (sig 0.05) in the perceptions of female and male students. Female students have a higher perception regarding the importance of using learning media based on local wisdom in learning chemistry. Likewise, students in classes X, XI, and XII showed differences in student perceptions (sig 0.05). Class XII students (4.01) have a higher perception than class XI students (3.98) and class X (3.97). Based on this research, it was concluded that SMA MIPA students in Sitaro Regency need chemistry learning media based on local wisdom.